2022
DOI: 10.3390/ijms23158344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Treatment with Flavonoids on Metabolic Syndrome Components in Humans: A Systematic Review Focusing on Mechanisms of Action

Abstract: Diets high in bioactive compounds, such as polyphenols, have been used to mitigate metabolic syndrome (MetS). Polyphenols are a large group of naturally occurring bioactive compounds, classified into two main classes: non-flavonoids and flavonoids. Flavonoids are distributed in foods, such as fruits, vegetables, tea, red wine, and cocoa. Studies have already demonstrated the benefits of flavonoids on the cardiovascular and nervous systems, as well as cancer cells. The present review summarizes the results of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 103 publications
0
26
0
1
Order By: Relevance
“…Suzuki et al [ 94 ] found a positive effect of black and green tea catechins on obesity. Quercetin and other flavonoids with antioxidant, anti-inflammatory, and hepatoprotective effects can effectively prevent metabolic diseases [ 95 , 96 , 97 ]. The intake of flavonoids can reduce the risk of metabolic syndrome disorders and rare side effects [ 95 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%
“…Suzuki et al [ 94 ] found a positive effect of black and green tea catechins on obesity. Quercetin and other flavonoids with antioxidant, anti-inflammatory, and hepatoprotective effects can effectively prevent metabolic diseases [ 95 , 96 , 97 ]. The intake of flavonoids can reduce the risk of metabolic syndrome disorders and rare side effects [ 95 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%
“…Another flavonoid of interest in ameliorating the signs of MS is quercetin due to its antihypertensive, antihyperlipidaemic, antihyperglycaemic, and other properties [ 37 ]. For more information, we recommend referring to the review by Gouveia et al [ 38 ].…”
Section: Metabolic Syndrome Managementmentioning
confidence: 99%
“…They are best-known for their antioxidant properties, but the range of their activity is much wider [ 2 , 23 ]. Many pre-clinical and clinical (both observational and intervention) studies have suggested, that increased intake of phenolic compounds is related to a lower risk of cardiovascular diseases, diabetes, cancer, and neurodegenerative diseases [ 24 , 25 , 26 , 27 ]. In the past, beneficial effects of polyphenols were attributed mainly to their antioxidant activity, but currently, evidence suggests that dietary intake might not provide a high enough concentration in tissues for radical-scavenging properties to be significant.…”
Section: Chemical Content Of Seedsmentioning
confidence: 99%